Desenvolvimento de interface em matlab: análise de estabilidade lateral de arcos em perfil I - Andrade, Gabriel Ferreira (Universidade Federal Rural do Semi-Árido, 2018)
In this work the formulation for the lateral stability calculation of arcs in profile I in steel is described. The equations were implemented in MATLAB. It aims to develop a graphical interface. Then, a comparative analysis was performed with the results obtained in MATLAB with values requesting an arc in I profile applied in FTOOL. Subsequently, a parametric analysis of the results found for variations of the properties of an arc is done, the study being limited to steel and the profile I as main restrictions. It was verified, from the mathematical expressions of Guo et al. (2015), that the arcs present critical loads of greater buckling proportional to the increase of the radius and smaller loads with the increase of the span of the arc. It was observed that the structures have greater resistance when applying profile I more robust. In addition, it can be seen that the lateral collisions in the arcs do not influence the resistance in their own plane, but, it presents greater difficulty of lateral deformation with a high number of locks. It was also verified the force intensity in the arc applied in the locks when it presents tendency to deformations.
Keywords: Flambagem; Carga crítica; Deformação lateral; Interface gráfica; Bending; Critical load; Lateral deformation; Graphic interface; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA